In Vitro Laser Treatment Platform Construction with Dental Implant Thread Surface on Bacterial Adhesion for Peri-Implantitis. (16th July 2017) - Kuo, Hsien-Nan; Mei, Hsiang-I; Liu, Tung-Kuan; Liu, Tse-Ying; Lo, Lun-Jou; Lin, Chun-Li
Abstract : This study constructs a standard in vitro laser treatment platform with dental implant thread surface on bacterial adhesion for peri-implantitis at different tooth positions. The standard clinical adult tooth jaw model was scanned to construct the digital model with 6 mm bone loss depth on behalf of serious peri-implantitis at the incisor, first premolar, and first molar. A cylindrical suite connected to the implant and each tooth root in the jaw model was designed as one experimental unit set to allow the suite to be replaced for individual bacterial adhesion. The digital peri-implantitis and suite models were exported to fulfill the physical model using ABS material in a 3D printer. A 3 mm diameter specimen implant on bacterial adhesion against Escherichia coli was performed for gram-negative bacteria. An Er:YAG laser, working with a chisel type glass tip, was moved from the buccal across the implant thread to the lingual for about 30 seconds per sample to verify the in vitro laser treatment platform. The result showed that the sterilization rate can reach 99.3% and the jaw model was not damaged after laser irradiation testing. This study concluded that using integrated image processing, reverse engineering, CAD system, and a 3D printer to construct a peri-implantitis model replacing the implant on bacterial adhesion and acceptable sterilization rate proved the feasibility of the proposed laser treatment platform.